CHARACTERISTICS OF PSYCHOMOTRICITY IN THE CONTEXT OF ATTENTION DEFICIT DISORDER WITH HYPERACTIVITY - CAROLINA BODEA HAŢEGAN (Studia Universitatis Babes-Bolyai, 2012)
ABSTRACT. This paper establishes the relation between two concepts, the concept of psychomotricity and ADHD, relation reflected by a case study. Fallowing this theoretical framework and detailing executive functions, there can be underlined the main aspects, necessary to be assessed in order to relate those two concepts. Thus, the assessment of the case study is focused on visual-graphical-motor areas, the results confirming us the possibility of relating ADHD and psychomotricyty as two connected concepts.